World Earth Summits - Herrera, Beatriz (2002)
The report 'Global Challenge, Global Opportunity' published by the United Nations-UN Organization, underscores the need to significantly increase efforts to support sustainable development that allows better management of world resources. The UN Secretary General and Chief for the aforementioned report, Nitin Desai, said: "If we do not do something to change our development patterns, we will put the security of the Earth and its inhabitants at risk in the long term." In this sense, the National University of San Marcos-UNMSM, gathering this concern, sponsored the first national forum on sustainable development, spreading its contents and looking for alternatives that contribute to the full application of the programs adopted in 1962 in Stockholm, in 1992 in Rio de Janeiro and recently in Johannesburg. In the city of Johannesburg, the Summit on Sustainable Development agreed to continue efforts to promote sustainable development, improve the lives of people living in poverty and reverse the continuing degradation of the global environment. In the face of increasing poverty and increasing environmental degradation, this event has been successful in urgently establishing and creating commitments and partnerships aimed at action, to achieve measurable results in the short term. In other words, ten years after the Rio Summit, the conditions for sustainable development were no better than those that prevailed in 1992, since it is observed that poverty is increasing, development needs are more pressing and the environment continues to degrade. Many specialists maintain with concern that the aspects of globalization are negative in many cases, due to the effects of the process such as financial and economic instability, social exclusion and the depletion of natural resources that are intensifying. Consequently, a significant part of the world is lagging behind in world development. Although a relative advance in poverty reduction was noted during the 1990s, as the number of people living on less than a dollar a day decreased from 1.3 billion to 1.2 billion, this advance was only concentrated in East Asia and However, certain regions have not yet manifested these trends in Latin America, such as Africa, which continues to experience the highest levels of mortality, poverty and hunger, and shows the greatest contrast, in comparison, with the living conditions of industrialized countries. The problem goes beyond living standards and has an impact on the situation of the natural resources of that continent, where the deforestation rate is the highest worldwide, with 7% of the forests during the decade of the ninety.